مساهمة أسلوب التكلفة على أساس الأنشطة (abc) في تحسين الأداء المالي للمؤسسة الاقتصادية -دراسة حالة مؤسسة النسيج والتجهيز Tifib بسكرة- - جحيش, يسرى; بوسكار, ربيعة (جامعة الوادي - University of Eloued, 2022)
This study aimed to know the role played by the activity-based costing (ABC) method in improving the financial performance of the economic institution, as it is one of the modern methods of cost accounting. In order to answer the problem of the study, the descriptive analytical method was relied on to study the reality of the TIFIB Institution of Textiles and Equipment in Biskra. Basis of activities The cost of products has been determined more precisely, which enables the organization to accurately allocate and distribute indirect costs and thus rationalize its costs and thus improve its profitability, which leads to the improvement of its financial performance
The contribution of the activity-based costing method (ABC) to improving the financial performance of the economic -institution -a case study of the TIFIB Textile and Equipment Corporation in Biskr
مقال
Keywords: التكاليف الحقيقية ; أسلوب التكلفة على أساس الأنشطة ; التكاليف المباشرة وغير المباشرة ; الربحية ; الأداء المالي; Actual costs ; activity-based costing method ; direct and indirect costs ; profitability ; financial performance